2013
DOI: 10.3892/ijo.2013.2168
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-126 functions as a tumor suppressor in colorectal cancer cells by targeting CXCR4 via the AKT and ERK1/2 signaling pathways

Abstract: Recent evidence shows that altered microRNA-126 (miR-126) expression is implicated in the progression of colorectal cancer (CRC). However, the precise roles and mechanisms of miR-126 in CRC remain unclear. The aim of this study was to investigate the roles of miR-126 in CRC cells and to elucidate miR-126-mediated mechanisms in CRC cells. First, miR-126 expression was analyzed using qRT-PCR in 4 human CRC cell lines (SW480, SW620, HT-29 and HCT-116). Furthermore, the biological properties of miR-126 in CRC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 35 publications
3
50
0
Order By: Relevance
“…In the present study, we found that miR-126 was downregulated in ECs and that its downregulation was induced by promoter hypermethylation of its host gene. Dysregulation of miR-126 has also been observed in other tumors, such as colon cancer (32) and lung cancer (33), but little is known about its function in ESCC. This is the first report to show that miR-126 is downregulated and acts as a new tumor suppressor in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that miR-126 was downregulated in ECs and that its downregulation was induced by promoter hypermethylation of its host gene. Dysregulation of miR-126 has also been observed in other tumors, such as colon cancer (32) and lung cancer (33), but little is known about its function in ESCC. This is the first report to show that miR-126 is downregulated and acts as a new tumor suppressor in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout of miR-126-3p can cause a loss in blood vessel integrity and result in hemorrhage during embryonic development in zebrafish, showing that miR-126-3p controls blood vessel integrity and angiogenesis [15]. Many studies have suggested that miR-126-3p plays a part as either an anti-oncogene or an oncogene in different cancers [16, 17]. miR-126-3p also acts as a tumor suppressor via the downregulation of intron 7 of epidermal growth factor-like domain 7 (EGFL7) and it may be a promising candidate for therapeutic strategies in oral squamous cell carcinoma [18].…”
Section: Introductionmentioning
confidence: 99%
“…Discussion dysregulated miRNA expression is responsible for the initiation and progression of several types of human cancers. Recent evidence has demonstrated that aberrant miRNA expression affects cell proliferation, invasion, apoptosis, and chemosensitivity (17)(18)(19). Among these miRNAs, miR-203 remains an important subject of investigation since its role as a tumor suppressor gene or oncogene remains largely undetermined.…”
Section: Overexpressed Mir-203 Induces Apoptosis and Decreases Cell Imentioning
confidence: 99%